2015
DOI: 10.1371/journal.pone.0115850
|View full text |Cite
|
Sign up to set email alerts
|

A Meta-Analysis of High Dose, Intermittent Vitamin D Supplementation among Older Adults

Abstract: BackgroundThe effects of intermittent, high dose vitamin D treatment in older adults have not been documented. We conducted a meta-analysis to provide a quantitative assessment of the efficiency of intermittent, high dose vitamin D treatment on falls, fractures, and mortality among older adults.MethodsElectronic databases were searched for randomized controlled trials (RCTs) on high dose, intermittent vitamin D supplementation among older adults. Two researchers independently screened the literature according … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
41
0
5

Year Published

2017
2017
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 50 publications
(47 citation statements)
references
References 34 publications
1
41
0
5
Order By: Relevance
“…This viewpoint was articulated in response to a well‐publicized study that showed that older women who received annual bolus dosing of 500,000 IU vitamin D for 3–5 years experienced more falls and fractures than the placebo group . On the other hand, a systematic review and meta‐analysis of vitamin D intervention trials concluded that high‐dose, intermittent vitamin D therapy did not affect all‐cause mortality among these older adults ≥65 years of age, nor was there any impact (benefit or adverse effect) observed regarding fractures or fall prevention, when compared to either no treatment or placebo . Of note, one study involving a single intramuscular injection of 600,000 IU revealed significant beneficial effects on functional neuromuscular performance, reaction time, and balance after 6 months, although muscle strength or incidence of falls did not improve .…”
Section: Interventions To Reduce the Prevalence Of Vitamin D Deficienmentioning
confidence: 99%
“…This viewpoint was articulated in response to a well‐publicized study that showed that older women who received annual bolus dosing of 500,000 IU vitamin D for 3–5 years experienced more falls and fractures than the placebo group . On the other hand, a systematic review and meta‐analysis of vitamin D intervention trials concluded that high‐dose, intermittent vitamin D therapy did not affect all‐cause mortality among these older adults ≥65 years of age, nor was there any impact (benefit or adverse effect) observed regarding fractures or fall prevention, when compared to either no treatment or placebo . Of note, one study involving a single intramuscular injection of 600,000 IU revealed significant beneficial effects on functional neuromuscular performance, reaction time, and balance after 6 months, although muscle strength or incidence of falls did not improve .…”
Section: Interventions To Reduce the Prevalence Of Vitamin D Deficienmentioning
confidence: 99%
“…Twelve reviews including 8-42 trials indicated that vitamin D may reduce falls risk, increase muscle strength and improve function, though evidence was mixed. [115][116][117][118][119][120][121][122][123][124][125][126] Some individual reviews suggested that vitamin D may be more effective when calcium is added 118,124 or in deficient populations, 120 while evidence was mixed regarding the effects of dose. 121,122 Long-term supplementation may be required for effects on mortality.…”
Section: Nutritionmentioning
confidence: 99%
“…Several trials using high-dose, intermittent vitamin D report an increase rather than a decrease in both falls and fractures [21]. This negative effect was observed in patients taking 500 000 once a year [4], and even 60 000 IU once a month [22].…”
Section: An Overview Of Evidencementioning
confidence: 99%